(untitled) (Science journal «Technical service of agriculture, forestry and transport systems», 2025)
The development of traction motors is an important direction in the improvement of transport vehicles. Traction motors are constantly improving in terms of electricity consumption and reliability and diagnostics, as well as reducing operating costs. This article pays special attention to methods for selecting the type of traction motor, assessing the quality of traction motors during design, manufacture and operation based on their vibration characteristics.